Wideband Frequency Synthesis Using Dual-Optical Phase-Locked Loop Synchronized to Optical Comb - Surendranath-Shroff, Vijayalakshmi; Bahmanian, Meysam; Scheytt, J. Christoph (2026 IEEE MTT-S Radio Frequency Systems and Applications Symposium (IMS RFSA))

Unpacking [Whose] Imaginary: Reflections from a Workshop on Digital Imaginaries - Menne, Anna Lena; Schulz, Christian

Soziales Lernen in der Grundschule - ein Praxisprojekt zur Entwicklung des PET - Paderborner Entwicklungstraining für Mensch und Tier. Ein Training zur Unterstützung der individuellen Entwicklung aller Beteiligten. - Mombeck, Mona; Caruso, Carina (Diskurse und Praktiken der Heterogenität. Pädagogisches Handeln in heterogenen Settings. Mit einem Fokus auf die Elementar- und Primarbildung)

Single-stage setting of blind rivet nuts without pre-drilling - Böhm, Yannic; Meschut, Gerson (Discover Mechanical Engineering)
Abstract The increasing use of thin-walled profiles in automotive battery housing construction is leading to a growing demand for one-sided access mechanical fasteners. Currently, the installation of blind rivet nuts still requires pre-drilling using chip-forming operations. In Meschut and Meyer (Vorlochfreies Setzen von Funktionselementen mittels Fließformen, Europäische Forschungsgesellschaft für Blechverarbeitung e.V. (EFB), Hannover, 2021), a chipless, two-step method for installing blind rivet nuts was developed, in which flow-drilling is the initial step. To eliminate the pre-drilling operation and optimise the joining process of blind rivet nuts, a pilot-hole-free joining method using a flow-drilling process is being pursued. The use of these blind rivet nuts can significantly simplify the joining process by eliminating chip-forming pre-drilling operations. Additionally, the screw-through capability reduces screw variance in automated fastening, optimising the feeding process by minimising the risk of incorrect screw selection. This work aims to develop a single-step process for the installation of a blind rivet nut. To achieve this, it is necessary to design the geometries of both the blind rivet nut and the flow-drill former, which also serves as the mandrel for the blind rivet nut. In addition to the geometries of the tools and functional elements, the flow-drilling process itself has been developed. Special attention is given to the pull-through and the formation of the closing head. To optimise the closing head formation, an iterative optimization process was used. The quality of the pull-through is improved by varying the tip geometries and adjusting the process parameters during flow-drilling.

Potenziale und Limitationen empirischer Forschung zu interreligiösen Lehr- und Lernprozessen in Schule und Hochschule - Meyer, Karlo; Caruso, Carina (Theo-Web)
Dieser Beitrag schließt an die anderen Artikel dieses Themenheftes an. Dabei werden mögliche Strukturen empirischer Forschung zu interreligiösen Lehr-Lernprozessen auf der Hochschulebene vorgeschlagen. Mögliche Zieloptionen, Ebenen und Fallstricke für die empirische Forschung zu interreligiösen Lehr-Lernprozessen werden diskutiert. Des Weiteren werden Erkenntnisse bisheriger Forschungsbemühungen zu interreligiösen Lehr-Lernprozessen zusammengefasst und ein strukturierter Ausblick auf Optionen empirischer Forschungen im universitären Bereich gegeben, wobei die vorangehenden Aufsätze dieses Themenheftes hinzugezogen werden.
Keywords: Interreligiöses Lernen; Lehr-Lernprozesse; Religionspädagogik; Hochschuldidaktik; empirische Forschung

Quantum speedup from nonclassical polarization - Aßbrock, Tim; Sperling, Jan; Ares, Laura (Physical Review Research)
We develop a framework for identifying nonclassical speedups in systems with polarization, likewise spin degrees of freedom. By confining the dynamics to the manifold of angular momentum coherent states, which act as the classical reference in this case, we compute the speed limit that bounds the rate of change of the state achievable without generating quantum coherence. A comparison with the unrestricted quantum speed limit enables the quantitative identification of speedups arising from polarization nonclassicality. We apply this framework to the cross-Kerr interaction, demonstrating a persistent speedup scaling as <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi mathvariant="script">O</a:mi> <a:mo>(</a:mo> <a:msqrt> <a:mi>N</a:mi> </a:msqrt> <a:mo>)</a:mo> </a:mrow> </a:math> with the photon number <c:math xmlns:c="http://www.w3.org/1998/Math/MathML"> <c:mi>N</c:mi> </c:math> , with a parity effect in favor of even photon numbers. The results establish polarization nonclassicality as a genuine dynamical resource, linking quantum coherence to quantum-enhanced evolution speeds in nonlinear photonic systems.

Generative Künstliche Intelligenz im Kontext von Lehren, Lernen und Beraten: Eine Perspektive der Pädagogischen Psychologie - Scheiter, Katharina; Bach, Katharina M.; Bauer, Elisabeth; Brod, Garvin; Bromme, Rainer; Buhl, Heike M.; Gagl, Benjamin; Greiff, Samuel; Hefter, Markus H.; Janke, Stefan; Lindner, Marlit A.; Mayweg, Elisabeth; et al. (Psychologische Rundschau)

Pólya--Schur problems and free probability - Campbell, Andrew; Jalowy, Jonas (arXiv:2605.31356)
In this work, we build a bridge between the Pólya--Schur program and Voiculescu's free probability theory. A cornerstone of the former is the Pólya--Benz Theorem, classifying a central family of real-root preserving operators on the space of polynomials, as those given by $f(\partial_z)$ for a Laguerre--Pólya function $f$ and the derivative operator $\partial_{z}$. We prove that any free (additive) infinitely divisible distribution can be attained as the weak limit of root distributions of Appell polynomials $f_n(\partial_z)z^n$ as $n→∞$, for a suitably chosen sequence $f_n$ of Laguerre--Pólya functions. Such questions on the (global) limiting distributions of real rooted polynomials belong to the active research area of finite free probability. In contrast to its standard tools, our approach allows for non-compactly supported limiting distributions, (barely) complex rooted polynomials and even provides the full microscopic description of the roots. Moreover, we extend our results to differential operators generating free multiplicative infinitely divisible distributions, to the rectangular free convolution, and to $f_n(\partial_z)p_n$ for real rooted polynomials $p_n$, implying a generalization of the recent connections between the heat flow and free Brownian motion to any free Lévy process. As corollaries, we identify free stable distributions by choosing $f_n$ to be a fixed rescaled Laguerre--Pólya function, and we prove various convergence results on the zero distributions of Jensen polynomials, e.g. the limiting root distribution of Jensen polynomial of the Riemann $Ξ$-function is given by the Cauchy distribution.

Box-covariances of hyperuniform point processes - Jalowy, Jonas; Stange, Hanna (Stochastic Processes and their Applications)

Der Wandmalereizyklus zu den Wissenschaften und Künsten in der Brandenburger Domklausur im Kontext - Heinrichs, Ulrike; Herrmann, Sabine; Schwieger, Olaf; Schumann, Dirk; Kuhn, Michaela; Knödler, Julia; Borchert-Pickenhan, Jens; Voigt, Martina; Stork, Hans-Walter; von Perger, Mischa; Knüvener, Peter; Fabritius, Helga; et al.

Three pitfalls in intercultural education: cultural uniformity, pedagogical neutrality, and presumptions of competence - Pöllmann, Andreas (Globalisation, Societies and Education)

Interkulturelle Pädagogik: Fallstricke, Potenziale und Forschungsgegenstände - Pöllmann, Andreas

Hybrid GaAs (111)/GaAs (100) PIN photodiodes for metasurface-assisted nonlinear upconversion detection - Spedt, Vladimir; Meier, Falco; Geromel, René; Mahler, Pascal; Henksmeier, Tobias; Reuter, Dirk; Zentgraf, Thomas; Meier, Cedrik (Optics Express)
Efficient detection of near-infrared light at telecommunication wavelengths remains a central challenge for GaAs-based photonic and optoelectronic devices due to the absence of linear absorption below the bandgap. Here, we demonstrate a hybrid nonlinear optoelectronic device that enhances the detection efficiency of a (001)-oriented GaAs PIN photodiode under telecommunication-wavelength illumination, where absorption is intrinsically limited to two-photon absorption (2PA). Our approach relies on the integration of a transferred, nanopatterned 385 nm-thick (111)-oriented GaAs nanofilm acting as an on-chip nonlinear frequency-conversion layer. Elliptical GaAs nanoresonators are employed to enhance second-harmonic generation (SHG) resonantly, converting incident 1550 nm radiation into above-bandgap photons efficiently absorbed by the underlying diode. Spatially resolved current–voltage measurements reveal a pronounced enhancement of the detector response in regions covered by the nanoantennas. The device exhibits a low dark current, while the metasurface-covered regions show the largest current response under 1560 nm excitation compared to the bare GaAs(100) diode and the unstructured GaAs(111) film. These results establish a direct functional link between dielectric metasurface–based nonlinear frequency conversion and electrical photodetection, providing a viable route toward integrated sub-bandgap detection schemes.

Experimental determination of kinking angles with out-of-phase mixed-mode loading by means of a novel specimen geometry - Krome, Sven; Kullmer, Gunter; Weiß, Deborah; Duffe, Tobias; Ostwald, Richard (Discover Mechanical Engineering)
Abstract The service life of fatigue-loaded components that already contain manufacturing‑induced microcracks is primarily governed by the direction and the rate of fatigue-crack growth. When multiple loading components (e.g., tension, compression, shear) act simultaneously but not in temporal synchrony, out‑of‑phase mixed‑mode conditions occur. Such loadings are typical for automotive chassis parts and mechanically joined sheet‑metal assemblies. For optimized design of structural components, the crack kinking angle that occurs under mixed‑mode loading must be predicted as accurately as possible. At present, however, this is still challenging for out‑of‑phase loading conditions. To investigate the associated crack kinking behavior, a novel Compact‑Tension‑Shear‑Mini (CTSM) specimen was developed, enabling controlled generation of plane out-of-phase mixed-mode loading states. Experiments were performed under various combinations of cyclic and static mode I and mode II load components and compared with the analytical predictions of the Out-of-Phase Mixed-Mode (OMM) concept. The measured crack kinking angles showed very good agreement with the predicted values, with mean deviations of only a few degrees, demonstrating the validity and reproducibility of the approach. These findings confirm the applicability of the OMM concept for describing fatigue‑crack propagation under non‑proportional mixed‑mode loading and provide a basis for fatigue‑life assessment of clinched joints and other cyclic multi-axially loaded components.

Influence of the R-Ratio and the Temperature on the Coefficients of a Novel Exponential Approach for the Formulaic Description of Fatigue Crack Growth Rate Curves - Kullmer, Gunter; Krome, Sven; Weiß, Deborah; Schramm, Britta; Ostwald, Richard (Metals)
Investigating crack growth in sheet metal originating from clinched joints is a major part of predicting the service life of mechanically joined structures. Clinching allows different materials to be joined together. A key task in this context is to perform crack growth simulations in the vicinity of clinched joints considering different load and environmental conditions. This requires formulaic descriptions of the fatigue crack growth rate curves for the materials used. For this purpose, fatigue crack growth rate curves for different R-ratios and temperatures are determined experimentally. Generally, these fatigue crack growth rate curves can be described very well using a novel two-part exponential approach for the formulaic description of fatigue crack growth rate curves developed at Applied Mechanics of Paderborn University (FAM). In this case, three parameters are sufficient to describe the fatigue crack growth rate curves. For the material HCT590X, which is frequently used in clinched joints, it is shown as an example how the parameters vary with the R-ratio and the temperature. In addition, at high crack growth rates, a significant rise in the fatigue crack growth rate curve sometimes occurs at both low and high temperatures. To account for this feature, the two-part exponential approach can be expanded to include a third part.

Exploring Mathematics Teacher Noticing of Whole-Class Discussions Across Career Stages - Becker, Federica; Bruns, Julia (Proceedings of the 49th Conference of the International Group for the Psychology of Mathematics Education: Research Reports. PME.)
Research on teacher noticing highlights differences between novice and expert teachers, yet little is known about early career and intermediate expertise levels and how these expertise-related differences emerge in central teaching tasks and content areas. Facilitating whole-class discussions represents a central teaching task, such as when fostering flexible strategy use. This study examines expertise-related differences in mathematics teachers’ noticing in observed video scenes of whole-class discussions on flexible strategy use in Grade 1 using Epistemic Network Analysis. The preliminary results show no substantial differences between intermediate and expert teachers but between beginning teachers and the other two expertise groups regarding their noticing focus and the cognitive structures underlying their noticing processes.

Development and Modification of Porous Polymer Structures in the Vicinity of Cellulose Fibers - Pusse, S.; Heinz, S.; Limprasart, W.; Gemmer, L.; Witayakran, S.; Schabel, S.; Presser, V.; Gutmann, Torsten; Gallei, M. (Polymer Chemistry)

Multivariate counting of wild abelian extensions - Gundlach, Fabian (arXiv:2607.27364)
Let $K$ be a global function field of characteristic~$p$ and let $G$ be a finite abelian group of exponent $p^e$. We show that the multivariate generating function counting sub-$G$-extensions of $K$ with respect to $e$ specific height functions (encoding successive drops in the exponents of the higher ramification groups) is rational.

Klaus Fuchs-Kittowskis Radikaler Digitaler Humanismus: Ein kritischer Ansatz im Forschungsbereich Informatik und Gesellschaft. - Fuchs, Christian (Wissenschaft zwischen Krieg und Frieden – Verantwortung für eine menschwürdige Technik- und Gesellschaftsforschung)

Discourses on Discursive Machines. Review of Mark Coeckelbergh and David J. Gunkel, Communicative AI: A Critical Introduction to Large Language Models - Thomas, Sven (Jahrbuch Technikphilosophie)